Pengaruh Komitmen Top Manajemen, Motivasi, Dan Pelatihan Terhadap Penerapan Gugus Kendali Mutu Di Rumah Sakit Jiwa Daerah dr. Arif Zainudin Surakarta - Martuti Martuti (Puslatbang KHAN, 2017)
This study aims to examine the presence or absence of the influence of Top Management Commitment, Motivation, and Training on the implementation of Quality Control (GKM) in Regional Mental Hospital dr. Arif Zainudin Surakarta. The design of this research is correlational research using quantitative approach. Based on the research background developed a theoretical model consists of 4 variables with 19 indicators and 3 hypotheses tested. The research population is 553 people (all employees of RSJD dr Arif Zainudin Surakarta), while the selected sample is 110 people in RSJD dr. Arif Zainudin Surakarta. The data were collected by using questionnaires and interviews to the respondents. Data analysis techniques used are multiple regression analysis with the help of software SPSS version 2014.The result of the research found that there is a positive influence of the Top Commitment Management, Motivation, and Training on the Implementation of Quality Control in RSJD dr. Arif Zainudin Surakarta. The dominant factor on the implementation of Quality Control Cluster is the Top Management Training, Motivation and CommitmentBased on the results of research, suggestions are submitted to: (1) Central Java Provincial Government, for the existing GKM in each OPD (Organization of Regional Devices) can be applied in tangible form, one of them by implementing the Convention of Quality Control or Degree of Work Culture among Organization Area; (2) Need to be implemented GKM training and motivation for all employees in RSJD dr. Arif Zainudin; (3) Regional Human Resource Development Agency of Central Java Province, it is necessary to develop a culture work culture management model by adding Quality Circle Materials.